GetSensorData: An extensible Android-based application for multi-sensor data registration - Juan D. Gutiérrez; Antonio R. Jiménez; Fernando Seco; Fernando J. Álvarez; Teodoro Aguilera; Joaquín Torres-Sospedra; Fran Melchor (SoftwareX, 2022)
Smartphones are powerful tools with extensive sensorization that can provide useful information in research or everyday life applications. This information can be obtained from the device’s built-in sensors or through other external sensors connected physically via USB or wirelessly via Bluetooth or WiFi. This paper presents the GetSensorData application that provides an open-source, flexible and extensible framework for registering sensor data from Android devices. The application uses standard formatting and synchronization, easing interoperability with other software. End developers (particularly those involved in research) can save the effort and time of creating their sensor acquisition applications and fully concentrate on the higher-level data processing tasks. The application has been used and successfully evaluated for six years by various research groups in different activities related to their work areas. Some examples are the calibration of positioning systems in competitions held at conferences, modeling wireless signal path loss propagation in indoor environments or data collection for unsupervised learning algorithms.